An exploration of experiences of living renal donors following donation - Williams, Anne; Colefax, L.; O'Driscoll, C.; Dawson, Sky (American Nephrology Nurses' Association, 2009)
The experiences of living renal donors in Western Australia were explored using the qualitative method of grounded theory. Data were collected through 18 tape-recorded interviews with donors. Two main categories were identified that related to the physical and psychological reactions that occurred following surgery. This study provides insights (both positive and negative) into the donation experience.